Rare Organism Uncommon Disease Case Vignette of Guillain–Barré Syndrome Induced by Fusobacterium nucleatum Infection - K. Shah; A. Ahmed; K. Kaveh; A. Frugoli; M. Hammoudi (Case Reports in Infectious Diseases)
In this case report, we describe an unusual pathogen F. nucleatum-induced empyema, followed by the development of Guillain–Barré syndrome (GBS). Although many pathogens have been associated with GBS, this may be one of the few in the literature to describe an association with F. nucleatum infection.